Path Loss Model for the Bananas and Weeds Environment Based on Grey System Theory - Pisit Phokharatkul (2022)
This paper presents a prediction of path loss for wireless sensor network (WSN) deployment in the bananas and weeds environment. The banana plant and weed density affect banana quality and productivity. The WSNs applied to detect the banana plant density and weeds density in the farm. The path loss predicted model derived from received signal strength (RSS) measurements at different distances using grey system theory. Grey system theory has the advantage of needing a little sample data and calculating no characteristic quantity. This model use to predict the banana plant density and weeds density. In addition, the proposed model is compared the traditional model. From the model, it found that the RSSs varied according to the density of banana plants and weeds including the height of bananas.